The Role of Geography in Understanding, Managing and Governing Disaster Related to Waste Management - Adura Tengku Hamzah, Tengku Adeline (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Geography has a long record of understanding, managing and governing disaster. The key element that connects geography and disaster is spatial distributions. Potential disasters and the physical and social impacts after any disaster events, can be described in spatial patterns. Many researches have shown that geography knowledge on spatial and scalar skills have been adopted and adapted in the processes of rescue, recovery and policy making of natural disaster around the world such as earthquake, landslide, forest fire and flooding. This paper seeks to elaborate a different perspective to the relation of geography and disaster. It intends to explain how geography is relevant and significant in the process of avoiding disaster related to new or man-induced disaster related to solid and hazardous waste management. Mapping skills and technology, as in GIS, has been adapted in siting the best location to build a solid waste landfill to avoid pollution, and the long-term and short-term disasters that it may bring. On the other hand, in managing transboundary hazardous waste, geography understanding of skills and scale has been useful in governing and decision making processes. The application of multiple level governance perspective in policy making as highlighted in this paper, stresses the complex web of interactions between state and non-state policy makers, which are operating at various levels of governance; indicating the significant of multidimensionality in policy making to avoid disaster due to hazardous material in e-waste.